2004
DOI: 10.1161/01.cir.0000138927.00357.fb
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Dobutamine Stress Magnetic Resonance, Adenosine Stress Magnetic Resonance, and Adenosine Stress Magnetic Resonance Perfusion

Abstract: Background-Dobutamine stress MR (DSMR) is highly accurate for the detection of inducible wall motion abnormalities (IWMAs). Adenosine has a more favorable safety profile and is well established for the assessment of myocardial perfusion. We evaluated the diagnostic value of IWMAs during dobutamine and adenosine stress MR and adenosine MR perfusion compared with invasive coronary angiography. Methods and Results-Seventy-nine consecutive patients (suspected or known coronary disease, no history of prior myocardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
151
0
6

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 295 publications
(168 citation statements)
references
References 27 publications
11
151
0
6
Order By: Relevance
“…The later development of wall motion abnormalities in this sequence suggests that stress p-MRI may be more sensitive in detecting CAD, and therefore more useful for prognosis than stress cine MRI. In diagnostic opportunities, several authors suggested that perfusion markers are more sensitive and wall motion abnormalities more specific for the detection of CAD [26,27]. In comparing the predictive power of positive stress test results, adenosine perfusion and dobutamine wall motion imaging were equally high [6].…”
Section: Discussionmentioning
confidence: 99%
“…The later development of wall motion abnormalities in this sequence suggests that stress p-MRI may be more sensitive in detecting CAD, and therefore more useful for prognosis than stress cine MRI. In diagnostic opportunities, several authors suggested that perfusion markers are more sensitive and wall motion abnormalities more specific for the detection of CAD [26,27]. In comparing the predictive power of positive stress test results, adenosine perfusion and dobutamine wall motion imaging were equally high [6].…”
Section: Discussionmentioning
confidence: 99%
“…Following acute MI, cine CMR with low-dose dobutamine can be used to assess viability (69) . Highdose dobutamine stress CMR has high predictive value in identifying LV wall motion abnormalities due to coronary stenosis (70) .…”
Section: Cine Imagingmentioning
confidence: 99%
“…It is commonly believed that adenosine causes a 'steal phenomenon' by increasing perfusion in coronary territories not affected by epicardial artery stenosis, which leads to relative hypoperfusion of the territory subtended by a stenosed coronary artery (33). Several research papers (34)(35)(36)(37)(38), including one multicentre study, have assessed the role of adenosine stress perfusion for the diagnosis of coronary artery disease and consistently demonstrated high sensitivity for CMR imaging to diagnose epicardial coronary artery stenoses. When CMR perfusion was compared with x-ray coronary angiography, its specificities to detect coronary stenoses were only moderately high (62% to 90%) (34)(35)(36)(37)(38).…”
Section: Detection Of Stress-induced Myocardial Ischemiamentioning
confidence: 99%
“…Several research papers (34)(35)(36)(37)(38), including one multicentre study, have assessed the role of adenosine stress perfusion for the diagnosis of coronary artery disease and consistently demonstrated high sensitivity for CMR imaging to diagnose epicardial coronary artery stenoses. When CMR perfusion was compared with x-ray coronary angiography, its specificities to detect coronary stenoses were only moderately high (62% to 90%) (34)(35)(36)(37)(38). However, when PET or fractional flow reserve on x-ray angiography were used as standards of truth, specificities were higher (94% [34] and 90% [38], respectively).…”
Section: Detection Of Stress-induced Myocardial Ischemiamentioning
confidence: 99%